Metabolomics, Oxidative, and Nitrosative Stress in the Perinatal Period - Kuligowski, Julia; Vento, Máximo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Studies focusing on the perinatal period face unique challenges, yet research in this area is extremely important, as this period of life is highly delicate and adverse events might have a long-lasting impact. With the advent of powerful high-resolution and high-throughput analytical methods, researchers have started to successfully develop and implement novel approaches in this area. New insights have great potential to be translated into novel diagnostic tools, as well as alternative preventive and treatment approaches. This book collects a series of timely review and original research articles focusing on metabolomic, oxidative, and nitrosative stress in the perinatal period.We would like to thank all involved authors for their high-quality contributions and their commitment to the publication of this work and hope that this book will be a useful resource for students, scientists, and doctors working in this specific area of application.